Role of trans-resveratrol in ameliorating biochemical and molecular alterations in obese rats induced by a high fructose/fat diet - Marwa Maher Khamis; Said Salama Moselhy; Shaimaa Rihan (Scientific Reports)
Abstract We evaluated the effect of trans-resveratrol (RSV) in ameliorating biochemical and molecular alterations in obese Wister male rats fed on high-fat/high-fructose-fed. Male Wister rats were divided into eight groups and fed with either a standard diet (control), high fructose (HF), high fat (HFAT), or a high- fructose high- fat (HF/HFAT) diet and supplemented with RSV (30 mg/kg/day) for 4 weeks. The food intake, body weight, glycemic parameters, lipid profile, oxidative stress were assessed. SIRT1 gene expression, PGC-1α, cyto-c and GLUT-4 were evaluated by qRT-PCR in adipose tissue of normal and obese rats. The body weight gain, serum fasting glucose, insulin, and HOMA-IR values were significantly higher in the HF and HF/HFAT groups than in the HFAT and control groups. Hyperlipidemia was observed in high calorie diets fed rats compared to control group. The levels of total cholesterol, triglycerides and LDL-c were significantly elevated while HDL- c was significantly decreased in HF & HF/HFAT groups compared to HFAT group. The levels of serum malondialdhyde (MDA) and superoxide dismutase (SOD) activity in adipose tissue were elevated in all groups compared to control group, particularly in the groups that were kept on a high fructose diets (HF, HF/HFAT). SIRT-1, PGC-1α, Cyto-c, and GLUT-4 genes levels were significantly down regulated in HF, HFAT & HF/HFAT groups compared to control group. Supplementation of T-RSV restored the alteration in carbohydrates-lipid metabolism as well as oxidative stress and upregulation of SIRT-1, PGC-1α, Cyto-c, and GLUT-4 genes. RSV is a promising treatment in the management of pathologic consequences of obesity from high-calorie diet consumption via molecular alteration of target genes.